(untitled) (Pedagogy of Higher and Secondary Education, 2000)
The system of joint educational activity of the school and extra school establishments have characterized in this work. The main direction given off and the most significant tendencies of process development are discovered. The potential possibilities and conditions of individual psychophysical realization and social needs of person are revealed.